Hippopotamus and livestock grazing near water points: consequences for vegetation cover, plant species richness and composition in African savannas - Kanga, Erustus M.; Ogutu, Joseph O.; Piepho, Hans-Peter; Olff, Han (Frontiers in Ecology and Evolution, 2023)
Large mammals, such as hippopotamuses (Hippopotamus amphibius), can significantly alter the landscape, vegetation composition, and structure in savannas through their grazing habits and ecosystem engineering effects, especially around rivers. However, livestock grazing can strongly change these effects, as seen in the Kenyan Maasai Mara Ecosystem. In this region, the increasing intensity of livestock grazing along local rivers, resulting from the transition of Maasai pastoralists from a semi-nomadic lifestyle to one based on pastoral ranches near the Maasai Mara National Reserve, may alter the impact of hippo grazing on riparian vegetation. We investigated the differences in vegetation structure, plant species richness and composition between landscapes predominantly grazed by hippopotami and livestock. We studied 25 transects, each measuring 5 km and having 13 sampling plots of 10 × 10 m2 located at varying distances from rivers in the reserve (n = 16) and pastoral ranches (n = 9). We measured the height and estimated the percent cover of grasses, forbs, shrubs, and bare ground, as well as plant species composition and richness and grazing intensity. Our results show that the riverine areas were more intensely and homogeneously grazed in the pastoral ranches than in the reserve, and in the dry than in the wet season in both landscapes. In addition, grazing intensity decreased with distance from rivers in the reserve in both seasons, but only in the wet season in the pastoral ranches. The mean plant species richness was similar in both landscapes and decreased linearly with distance from rivers, but varied with grazing intensity due to differences in forb and shrub species. However, plant species composition differed significantly between the reserve and the pastoral ranches. Furthermore, species similarity indices declined with increasing distance from water. These results suggest that the effects of livestock and hippo grazing intensity on vegetation structure and spatial heterogeneity interact, and vary with landscape and season. While both hippopotamus and livestock grazing can modify riparian vegetation, livestock grazing impact on plant species composition, vegetation structure, and spatial heterogeneity appears to be more persistent, declining less rapidly with increasing distance from water. Consequently, hippo and livestock differentially impact landscape heterogeneity.